The Association of Early Life Socioeconomic Position on Breast Cancer Incidence and Mortality: A Systematic Review - Akinyemiju, Tomi F. (Int J Public Health, 2017)
OBJECTIVE: We conducted a systematic review of the literature relating early life socioeconomic position (SEP) to breast cancer incidence and mortality from a critical period and life course trajectory perspective. METHODS: PubMed, EMBASE and Web of Science were searched to identify cohort studies that evaluated the impact of early life SEP indicators on the incidence and/or mortality from breast cancer in adulthood. RESULTS: Nine distinct studies evaluated the relationship between early life SEP and breast cancer between 1990 and 2016. Five reports assessed breast cancer incidence and five assessed breast cancer mortality as outcomes; one study assessed both incidence and mortality. While lower early life SEP was associated with reduced breast cancer incidence and increased breast cancer mortality in the US, studies conducted in Europe were unable to establish a consistent association. CONCLUSIONS: We found moderate support for the association between early life SEP and incidence and mortality from breast cancer. The impact of early life SEP on breast cancer incidence and mortality appeared to vary between countries. We urge further investigation of the role of lifelong SEP trajectories in breast cancer outcomes.